Dietary medicinal plants enhance the chemical composition and quality of broiler chicken meat - TASHLA, T.; PUVAČA, N.; LJUBOJEVIĆ PELIĆ, D.; PRODANOVIĆ, R.; BOŠKOVIĆ, J.; IVANIŠEVIĆ, D.; JAHIĆ, M.; MAHMOUD, O.; GIANNENAS, I.; LEVIĆ, J. (Journal of the Hellenic Veterinary Medical Society, 2020)
The use of nutritional strategies to improve the quality of meat is a relatively new approach that has emerged at the interface of animal science and food science. The effects of dietary medicinal plants (Allium sativum L., Piper nigrum L., and Capsicum annuum L.) addition to chicken nutrition on quality characteristics of breast and thigh with drumstick meat, as well as caloric value of chicken meat were investigated. Quality measurements included meat sensory (colour, smell, taste, softness, chewiness, juiciness and overall impression), physical (pH, colour-CIE L*a*b* and drip-loss) and chemical (moisture, protein, fat and ash content) characteristics. Herbs showed significant (P < 0.05) influence in altering most examined quality parameters of chicken meat, especially when adding red hot pepper. Caloric value of chicken meat was improved which makes garlic, black pepper and hot red pepper valuable natural feed additives in improvement of meat quality as well as a natural growth promoter. In conclusion, herbs had positive influence on chicken meat quality, however the knowledge of their mode of action is still limited and thus requires further investigation.